2011
DOI: 10.1007/s11581-011-0521-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of LiFePO4/3-dimensional carbon nanostructure composites as possible cathode materials for Li-ion batteries

Abstract: Composites of three-dimensional (3D) carbon nanostructures coated with olivine-structured lithium iron phosphates (LiFePO 4 ) as cathode materials for lithium ion batteries have been prepared through a Pechini-assisted reversed polyol process for the first time. The coating has been successfully performed on nonfunctionalized commercially available 3D carbon used as catalysts. Thermal analysis revealed no phase transitions till crystallization occurred at 579°C. Morphological investigation of the prepared comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Following the previously results [17] we report, for the first time, the synthesis of 3D carbon foams-LiFePO 4 composites (hereafter CF-LFP), prepared by the Pechini-assisted reversed polyol method, using water as solvent. For comparison, pure LiFePO 4 (hereafter LFP) has been also prepared under similar conditions.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Following the previously results [17] we report, for the first time, the synthesis of 3D carbon foams-LiFePO 4 composites (hereafter CF-LFP), prepared by the Pechini-assisted reversed polyol method, using water as solvent. For comparison, pure LiFePO 4 (hereafter LFP) has been also prepared under similar conditions.…”
Section: Introductionmentioning
confidence: 85%
“…Recently Dimesso [17] has reported the preparation of composites of three-dimensional amorphous carbon coated with LiFePO 4 by a Pechini-assisted reversed polyol method. The process consists of a very simple citrate gel method by using simple water soluble inorganic salts, the process utilizes the ability of certain ␣-hydroxycarboxylic acids, such as citric acid, lactic and glycolic acids to form polybasic acid chelates with transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been used to prepare olivine structured LiMPO 4 powders and composites including Pechini method and modified Pechini methods. For M = Fe our group (Dimesso et al 2011a) reported the preparation of powders and composites using three-dimensional Vulcan carbon black prepared by a "the Pechini-assisted reverse polyol method" in which the LiFePO 4 (LFPO4) powder was prepared by dissolving in water Li(CH 3 COO)Á2H 2 O (lithium acetate) and Fe (SO 4 ) 2 *7H 2 O (iron(II) sulfate) as precursors with citric acid (2 x mol [Fe]), then adding DEG till the water weight percentage reached the desired value (10-40 % wt). Finally, phosphoric acid in equimolar ratio with Li and Fe ions was added.…”
Section: Lithium Transition Metal Phosphates As Cathode Materials Formentioning
confidence: 99%
“…A detailed description of the Pechiniassisted reverse polyol method has been previously reported. 35,36 As alternative, the sol-gel process can be carried out in organic solutions. The polyol method in the synthesis of the Scheme 1 Overall scheme for the synthesis of a 3D aligned LiMPO 4 (M = Fe, Co, Ni)-CNT composite cathode architecture.…”
Section: Deposition Process Of the Cathode Materials On The Carbon Na...mentioning
confidence: 99%